Assembling hollow carbon sphere-graphene polylithic aerogels for thermoelectric cells. (September 2017) - Dong, Dapeng; Guo, Haitao; Li, Guangyong; Yan, Lifeng; Zhang, Xuetong; Song, Wenhui
Abstract: Aerogels are highly porous bulk materials assembled chemically or physically with various nanoscale building blocks and thus hold promise for numerous applications including energy storage and conversion. Assembling of hollow or porous particles with the diameter larger than 100 nm into hierarchically porous aerogels is efficient but challenging for achieving a high specific surface of aerogel. In this regard, submicron-sized carbon spheres with hollow cores and microporous shells are assembled into bulk aerogels, for the first time, in the presence of two-dimensional graphene sheets as special cross-linkers. The resulting bead-to-sheet polylithic aerogels show ultra-low density (51–67 mg cm −3 ), high conductivity (263–695 S m −1 ) and high specific surface area (569–609 m 2  g −1 ). An application of thermocells is demonstrated with maximum output power of 1.05 W m −2 and maximum energy conversion efficiency of 1.4% relative to Carnot engine, outperforming the current simple U-shaped thermocells reported elsewhere. Graphical abstract: Hollow carbon spheres with microporous shell have been assembled with 2D graphene sheets into polylithic aerogels. The well controlled hierarchical porous structure and outstanding properties of the aerogels hold promise for high-efficient energy storage and conversion. Highlights: Assembling carbon aerogel with well controlled hierarchically interconnected network using submicron-sized hollow particles. Hollow carbon spheres and graphene have been assembled into bead-to-sheet polylithic aerogels. The best performance of the U-shape thermoelectric cells based on the polylithic aerogel have been fabricated so far.